2019
DOI: 10.1016/j.tafmec.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between cohesive zone and coupled criterion modeling of crack initiation in rhombus hole specimens under quasi-static compression

Abstract: Numerical predictions of initiation loading and crack length in a rhombus hole specimen made of a brittle material under quasi-static compression using either cohesive zone model or coupled criterion based on finite fracture mechanics are compared. Both methods lead to the conclusion that crack initiation results in a crack jump over a finite length at a given loading level, which depends on the material parameters and on the specimen geometry. The initiation load level and crack extent depend on the cohesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Over the past decades, the approach has been applied or extended successfully to a large variety of problems, both in static and fatigue, by considering different materials, features and loading conditions, e.g., to rounded V-notches made of ceramic, metallic and plastic materials [36,37], crack at interfaces and at bi-material junctions [38,39], 3-D failure onset from sharp V-notch edge [40], failure initiation at the atomic scale by means of molecular simulations [41], multiaxial loading conditions and notch sensitivity [42,43], moderate and large scale yielding regimes [44]. Furthermore, FFM predictions have been recently proved to be very close to those by the powerful cohesive zone model (CZM) in different research frameworks [45][46][47][48], so one can use FFM for preliminary sizing in structural design, letting the CZM for subsequent study refinements. By considering the advantages of the FFM approach and the similitude with other methods successfully applied to small scale specimens, it is worth investigating the validity of the FFM at the nanoscale.…”
Section: Introductionmentioning
confidence: 83%
“…Over the past decades, the approach has been applied or extended successfully to a large variety of problems, both in static and fatigue, by considering different materials, features and loading conditions, e.g., to rounded V-notches made of ceramic, metallic and plastic materials [36,37], crack at interfaces and at bi-material junctions [38,39], 3-D failure onset from sharp V-notch edge [40], failure initiation at the atomic scale by means of molecular simulations [41], multiaxial loading conditions and notch sensitivity [42,43], moderate and large scale yielding regimes [44]. Furthermore, FFM predictions have been recently proved to be very close to those by the powerful cohesive zone model (CZM) in different research frameworks [45][46][47][48], so one can use FFM for preliminary sizing in structural design, letting the CZM for subsequent study refinements. By considering the advantages of the FFM approach and the similitude with other methods successfully applied to small scale specimens, it is worth investigating the validity of the FFM at the nanoscale.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, studies [ 36 , 37 , 38 ] have shown that the mesh size of cohesive elements can affect the accuracy of the results. The material characteristic length is predicted as [ 37 , 38 ]: where is the Young modulus of the material, is the critical energy release rate, and is the maximum interfacial strength. Hence, can be obtained, and it is 37.66 mm.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Crack length lower bound Crack length upper bound rate G when l → 0. Note that G can be expressed as a function of G inc [15,20,21,23], which can be useful to study crack propagation after initiation. However, this point will not be treated in this work which is exclusively dedicated to the prediction of crack initiation.…”
Section: Energy Criterion Fulfilled Initiation Configurationmentioning
confidence: 99%
“…However, the asymptotic approach is only valid if the crack length remains small compared to the characteristic structure dimensions [19]. Moreover, the MA approach allows computing the initiation configuration but is unable to deal with unstable crack propagation that possibly occurs after initiation, which can be accounted for using the FFE approach [15,20,21,22,23,24]. Some authors compared the MA and FFE implementation of the CC.…”
Section: Introductionmentioning
confidence: 99%